Maintaining and improving mouth care for care home residents: A participatory research project. (24th June 2021) - Griffiths, Alys Wyn; Devi, Reena; Cheetham, Biddy; Heaton, Lisa; Randle, Angela; Ellwood, Alison; Douglas, Gail V. A.; Csikar, Julia; Vinall‐Collier, Karen; Wright, Judy; Spilsbury, Karen
Abstract: Background: Many people residing in nursing or residential care homes (also called long‐term care facilities) live with physical or cognitive difficulties. Staff working in these environments often help residents (particularly those with more advanced dementia) with their personal care needs, including maintaining mouth care and health. Poor oral health is associated with many difficulties, including increased risk of respiratory problems, pain and discomfort. Yet, concerns have been raised that staff may not have the knowledge and skills to effectively support residents with oral care and health. There is therefore an important gap between what is known about the importance of maintaining oral health (scientific evidence) and daily practice in long‐term care environments. Objectives: To work with care home staff: (1) to create a learning culture to address how to promote mouth care for residents, particularly when a resident resists support with this aspect of care; and (2) to effect mouth care practice changes (if required) using participatory and inclusive research cycles. Methods and results: We conducted a participatory research project to address this important area of care. Four participatory research 'cycles' were conducted. Cycle one explored existing literature to develop accessible guidance on strategies that staff could use to support residents to maintain and improve oral care, particularly when a resident may resist such care. Cycle two built on this review to determine knowledge levels within the care team. This highlighted deficiencies in staff knowledge, skills and competence for providing mouth care and their need for training to address this. Cycle three identified evidence‐based strategies to develop staff understanding and knowledge. Cycle four brought together experts from nursing, dentistry, behaviour change, systematic reviews and care homes research to develop a grant application to progress this work further. Conclusion: This paper provides an example of the processes undertaken in a participatory research project, bringing together science and practice to improve an essential area of care. Implications for practice: Using participatory research approaches in this setting can allow the effective translation of uncertainties in care and practice into questions that can be addressed by research, leading to meaningful outcomes for those living and working in care homes.